Competitiveness and current account adjustments in the euro area - Tobias Böing; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2016)
We empirically assess the impact of competitiveness measured by unit labor costs for current account balances in the Euro area. For this purpose, we estimate a panel with annual observations from 2000 to 2013. Our findings confirm the importance of competitiveness: Higher unit labor costs growth leads to lower current account balances. By splitting up unit labor costs growth in wage growth and productivity growth, we find wage growth and productivity growth to have a significantly negative and positive effect, respectively. However, the effect of unit labor costs is mainly driven by productivity growth, so that wage cuts are relatively ineffective and painful to fight current account deficits. But pushing productivity is also likely to be ineffective, since its positive effect for the current account may be offset by its effect on wages and GDP, which decreases current account balances.
Keywords: F32; E69; C33; 330; Euro Area; Competitiveness; Unit Labor Costs; Wage Growth; Labor Productivity Growth; Current Account; Panel